Analysis of Business Position to Determine The Marketing Strategy at The Kunja Villas and Spa Seminyak Bali - Putu Sulastri, Ida Ayu; Nyoman Wiantara, I Gusti (Jurnal Manajemen Pelayanan Hotel, 2022)
In every company or industry it is important to formulate a business strategy by analyzing the external and internal environment. Research on positions at The Kunja Villas and Spa Bali aims to find out what strategies are suitable to be implemented at The Kunja Villas and Spa. Through this research it is hoped that it can provide input for management to further optimize existing marketing strategies and be more aggressive in promoting new products to obtain optimal results in accordance with the goals and targets of The Kunja Villas and Spa. Based on the application of this research methodology, the results of interviews, questionnaires, documentation and quantitative data obtained from primary and secondary sources were analyzed descriptively with improvements through SWOT analysis and the Grand Strategy Matrix as instruments for conducting strategy analysis. The results of the analysis on internal and external strategic factors at The Kunja Villa and Spa, the position of the internal environment is in an average position with a value of 2.75 and the position of the external environment is in a high position with a value of 3.12. The meeting between the EFAS and IFAS total scores is in the second cell position (II), namely growth (concentration with horizontal integrity). In cell II it is categorized in a growth strategy where the strategy that can be carried out is by increasing access to a wider market by utilizing technology, developing new products, and improving the services offered. Keywords : Internal Factors, External Factors, SWOT Analysis, Marketing Strategy